2018
DOI: 10.1186/s13104-018-3373-y
|View full text |Cite
|
Sign up to set email alerts
|

A single-arm pilot study of guided self-help treatment based cognitive behavioral therapy for bulimia nervosa in Japanese clinical settings

Abstract: ObjectiveGuided self-help treatments based on cognitive behavioral therapy (CBT-GSH) are regarded as a first-line effective treatment for bulimia nervosa (BN). With limited application for CBT-GSH in Japanese clinical settings, we conducted a single arm pilot study in order to confirm the acceptability and availability of CBT-GSH in Japan.Results25 women with BN received 16–20 sessions of face-to-face CBT-GSH. Primary outcomes were the completion rate of intervention and abstinence rates from objective bingein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 21 publications
(24 reference statements)
3
16
1
Order By: Relevance
“…The results of this research are consistent with a previous RCT in the United States that used ICBT via videoconference and reported reductions in combined objective binge and purging episodes, objective binge episodes, and purging episodes (69%, 68%, and 70%, respectively) [18]. Our previous study with face-to-face CBT reported reduced combined objective binge and purging episodes, objective binge episodes, and purging episodes (51%, 50%, and 52%, respectively) [8]. This study has resulted in changes similar to our previous study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of this research are consistent with a previous RCT in the United States that used ICBT via videoconference and reported reductions in combined objective binge and purging episodes, objective binge episodes, and purging episodes (69%, 68%, and 70%, respectively) [18]. Our previous study with face-to-face CBT reported reduced combined objective binge and purging episodes, objective binge episodes, and purging episodes (51%, 50%, and 52%, respectively) [8]. This study has resulted in changes similar to our previous study.…”
Section: Discussionsupporting
confidence: 90%
“…The protocol included the following modules: assessment; explanation of CBT, motivation and goal setting, education on bulimia nervosa and how to keep a dietary diary, psychological education and monitoring for overeating behavior, psychological education and monitoring of diet, reforming of dietary habits (mindful diet), psychological education and self-monitoring of compensatory behavior, stress management and relaxation, understanding perfectionism, interpersonal relationships and assertions, acquisition of skills to associate with emotions (emotional adjustment, mindfulness, tolerance of distress, alexithymia), attention to body image, and prevention of recurrence. These modules are a development of those used in our previous study of face-to-face CBT for patients with bulimia nervosa in Japan [8,35].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A sample size of 140 with 70 per group is estimated be sufficient to test the hypothesis based on previously published BN remission rates of 45% for CBT-E and 25% for TAU [29]. A sample size of 66 patients per treatment group is required to detect a difference of this magnitude with an 80% power for the primary analysis.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…There have been few studies regarding the effects of psychological treatments for EDs in Japan. A single-arm pilot study provided preliminary evidence about the feasibility of guided self-help treatments based on CBT [29], but there have been no RCTs of psychological treatments that include formal protocols or treatment manuals. The lack of supporting evidence is most likely one of the reasons that ED-focused CBT has not been widely implemented in Japan.…”
Section: Introductionmentioning
confidence: 99%